Comparative Study of Flux‐Switching Permanent Magnet Machine with C‐ and E‐Shaped Cores Based on Magnetic Field Modulation Theory. Issue 2 (17th October 2022) - Wang, Peixin; Hua, Wei; Wang, Guangchen; Zhang, Zhiheng; Hu, Mingjin
Abstract : Due to high power density, favorable permanent magnet cooling capability, and essentially sinusoidal electromotive‐force (EMF) waveform, the flux‐switching permanent magnet (FSPM) machine has aroused wide interest around the world. In this article, to obtain a better topology of the FSPM machine, three FSPM machines, namely 12/10 C‐shaped core, 12/10 E‐shaped core, and 24/10 E‐shaped core FSPM machines, are investigated and compared. First, based on magnetic field modulation theory, the air‐gap modulation magnetic fields as well as their harmonic distribution of the three FSPM machines are modeled and investigated based on magnetic field modulation theory. Then, the optimal rotor tooth widths of the three FSPM machines are determined by finite element analysis. Finally, under the same conditions such as main dimensions, current density, and slot full ratio, the main performances including cogging torque, back‐EMF, output torque, overload capacity, and loss of the above three FSPM machines are predicted and compared, resulting in that the 12/10 E‐shaped core FSPM machine is capable of the best performance under rated condition. In addition, experiment verification on a 12/10 C‐shaped core FSPM prototype machine is conducted. © 2022 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.